2011
DOI: 10.1128/aac.01771-09
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Clinically Relevant Gram-Positive Anaerobic Cocci Collected over a Three-Year Period in the Netherlands

Abstract: The susceptibility of 14 species of 115 Gram-positive anaerobic cocci (GPAC) was determined for 14 antibiotics. To assure correct identification, strains were genotypically identified by fluorescence in situ hybridization and sequencing. Susceptibility differences (MIC 50 and MIC 90 ) for penicillin G, clindamycin, tigecycline, levofloxacin, amoxicillin-clavulanic acid, cefoxitin, ertapenem, meropenem, metronidazole, and doxycycline were found for the three clinically most relevant GPAC species: Finegoldia mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 20 publications
(19 reference statements)
5
26
1
1
Order By: Relevance
“…Remarkably, in this study P. harei showed the highest resistance for clindamycin (Table 3, 21%) which is in contrast to previous studies in which no resistance to clindamycin was found [5,8]. P. harei clindamycin resistance increased from about 10% in 2011 and 2012 to 40% in 2013.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Remarkably, in this study P. harei showed the highest resistance for clindamycin (Table 3, 21%) which is in contrast to previous studies in which no resistance to clindamycin was found [5,8]. P. harei clindamycin resistance increased from about 10% in 2011 and 2012 to 40% in 2013.…”
Section: Discussioncontrasting
confidence: 84%
“…The proportions of the other prevalent species within this group are similar. The proportion of the most prevalent GPAC strains F. magna, P. micra and P. harei are comparable with previous data [5,8]. It is difficult to compare the proportion of P. harei with other studies, because it is difficult to identify this species with phenotypic methods [9].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the type strain of P. asaccharolyticus (ATCC 14963) is not representative of the species and a low DNA-DNA homology between clinical isolates and the type strain was described. Thus, a number of type strains were reidentified using 16S rRNA gene sequencing and the closest relative for the strains was P. harei (Veloo et al, 2011a). Peptoniphilus harei and P. asaccharolyticus share the same biochemical features and it was concluded that the isolates of P. asaccharolyticus were misidentified.…”
Section: Description and Overviewmentioning
confidence: 99%